Modeling and analysis of profit based self scheduling of GENCO in electricity markets with renewable energy penetration and emission constraints. (February 2018) - Srikanth Reddy, K.; Panwar, Lokesh; Panigrahi, B.K.; Kumar, Rajesh
Abstract: In the rapidly evolving modern grid technologies and deregulated electricity markets, sustainability needs are given a prime importance besides achieving energy sufficiency. To investigate the same, a multi-objective function, including both economic as well as environmental interests is formulated. Pertaining to the inclusion of renewable energy technologies (RETs), constraints and penetration bounds are introduced. In addition, to examine the tradeoff criteria in preservation of environmental and economic interests, pareto sets are obtained and also, a simple optimality condition for selection of near optimal solution from the obtained pareto set is proposed. Further, various scheduling alternatives/scenarios and cases are proposed to analyze the scheduling scenarios against operation strategies of different markets. Simulation results are presented and discussed in detail. Observations of the pareto sets revealed that, RET schedules in pareto dominant solutions are affected by scheduling scenario. The intervention of RET affected the optimal tradeoff between economic and environmental interests. Therefore, optimal scheduling pertaining to particular scenario affects the energy schedule of both conventional, RET and thereby affecting resultant profit and emissions. Highlights: Market participation strategy for conventional and renewable energy is developed. Different market operation and participation mechanisms are introduced. Different scheduling scenarios based on Eco-Economic interests are discussed. A simple tradeoff criteria is proposed for optimal solution identification. Sensitivity analysis is performed with respect to various system parameters.